Assessing Functional Connectivity Dynamics During Cognitive Tasks Involving the Dorsal Stream - Huifang E. Wang; Jorge Gonzalez-Martinez; Viktor Jirsa; Patrick Chauvel; F.-Xavier Alario; Catherine Liegeois-Chauvel (Entropy, 2025)
Functional connectivity and its dynamic reconfiguration during cognitive tasks offer valuable insights into the neural mechanisms underlying cognitive functions. The dorsal language stream plays a crucial role in linking auditory and visual information with motor functions during language-related tasks. In this study, we investigated the dynamic functional connectivity of brain regions within the dorsal stream across five cognitive tasks using invasive stereoelectroencephalography (SEEG) recordings from patients with drug-resistant epilepsy. Our results reveal distinguishable functional connectivity patterns across various cognitive tasks using clustering algorithms. Furthermore, we were able to identify specific cognitive tasks based on their unique functional connectivity signatures, with a median of accuracy 0.91. Additionally, we identified key brain regions with strong connectivity roles and high variability across tasks. We analyzed source (out-degree) and sink (in-degree) regions during the picture naming, ba/pa, and oddball tasks, highlighting both shared and task-specific connectivity patterns. Among the twenty or so brain regions displaying a median in- and out-degree > 0.5 during the three tasks, the middle frontal gyrus (MFG) was highly involved in all three, corroborating its critical role in cognition. In contrast, the left superior frontal gyrus (SFG) and the superior temporal gyrus appeared to be modulated specifically via the tasks, exhibiting greater activity during picture naming compared to the other tasks. These findings enhance our understanding of the dynamic connectivity profiles associated with cognitive processing within the dorsal stream.